Naegeli-Franceschetti-Jadassohn syndrome: A rare case - Bela J Shah; Ashish K Jagati; Neha P Gupta; Suyog S Dhamale (Indian Dermatology Online Journal, 2015)
Naegeli-Franceschetti-Jadassohn Syndrome (NFJS) is a rare, autosomal dominant inherited form of ectodermal dysplasia, caused by mutation in the KRT14 gene. We report here a case of NFJS in a 27-year-old male who presented with reticulate hyperpigmentation over skin, dental changes, absence of dermatoglyphics, hypohidrosis, and hair changes.